Peran Pemerintah Desa Olehsari Kecamatan Glagah Dalam Meningkatkan Sumber Daya Manusia (SDM) Melalui Beasiswa Aparatur Desa - Zaki Al Mubarok; Moh. As’adi; Gustin Ayu Perwitasari (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
This research aims to determine how the role of the village government in improving human resources (HR) and supporting and inhibiting factors of the role of the village government in improving human resources (HR) in Olehsari Village, Glagah District, Banyuwangi Regency. The research method used in this study is qualitative research. Data collection techniques used in this study are observation, interview and documentation techniques. The instrument in this study is the researcher himself. While the data analysis applied in this study is interactive analysis, namely, data collection, data reduction, and conclusions. The results of this study show that the Government of Olehsari Village, Glagah District, Banyuwangi Regency has shown an important and proactive role in efforts to improve human resources (HR) through scholarship programs. Inhibiting factors in the implementation of this scholarship program include budget constraints, lack of information and counseling, bureaucracy and administrative constraints and lack of community involvement. Nevertheless, strong commitment and cooperation are expected to continue to encourage sustainable development and community welfare in the Olehsari Village Government, Glagah District, Banyuwangi Regency.